1999
DOI: 10.1046/j.1365-2095.1999.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dietary protein : lipid ratio on growth and nutrient utilization in gilthead seabream (Sparus aurataL.)

Abstract: Gilthead seabream Sparus aurata L. (initial mean body weight: 42.5 g) were fed four experimental diets containing either 47 or 51% of dry matter (DM) as protein and either 15 or 21% as lipid for 12 weeks. Each diet was hand‐distributed to triplicate groups of 60 fish, three times a day until satiation. The digestibility coefficients of the dietary components were determined using chromic oxide as a marker. The levels of protein or lipid in the diets did not affect the digestibility. Fish regulated their feed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
79
2
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 28 publications
30
79
2
13
Order By: Relevance
“…In different species, it has been observed that when the diet is low in energy or in an essential nutrient for growth such as proteins, the animal compensates such deficiency by increasing its consumption (GUILLAUME et al, 2004). According to SANTINHA et al (1999), when a fish is fed to satiety, weight gain will depend not only on the energy and nutrient content of the diet, also in its ability to regulate food intake. Consequently, these theories could explain the higher feed ingestion by P. brachypomus fed diets isoenergetics with low protein.…”
Section: Resultsmentioning
confidence: 99%
“…In different species, it has been observed that when the diet is low in energy or in an essential nutrient for growth such as proteins, the animal compensates such deficiency by increasing its consumption (GUILLAUME et al, 2004). According to SANTINHA et al (1999), when a fish is fed to satiety, weight gain will depend not only on the energy and nutrient content of the diet, also in its ability to regulate food intake. Consequently, these theories could explain the higher feed ingestion by P. brachypomus fed diets isoenergetics with low protein.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained in this study are consistent with those of Izquierdo et al (10), who investigated sea bream fingerlings fed with a vegetable oil mixture. Other studies (11,12) examined the effect of protein and fat rate used in sea bream feed on growth and revealed that feed conversion ratio increases in parallel with the increase of protein level. Similarly, it was determined that soybean, sunflower, and fish oil added to fish feed of sea bass at different rates did not have a significant impact on growth performance (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…According to Santinha et al (1999) an increase in dietary lipid content leads to a significant decrease in feed intake. However, in the present study no significant difference (p>0.05) in food intake was observed.…”
Section: Discussionmentioning
confidence: 99%